Communicative component of professional competence of future economists - Шепеленко, Тетяна (Pedagogy of Higher and Secondary Education, 2014)
Shepelenko T. L. Communicative component of professional competence of future economists. The article reveals the essence of the communicative component of professional competence of future economists. The author describes its structural components, defines pedagogical conditions of effective forming communicative competence.